2020
DOI: 10.1016/j.bcp.2020.114227
|View full text |Cite
|
Sign up to set email alerts
|

AR12 (OSU-03012) suppresses GRP78 expression and inhibits SARS-CoV-2 replication

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 32 publications
4
46
0
1
Order By: Relevance
“…2G ). Interestingly, a recent study showed GRP78 co-localizing with SARS-2-S following live virus infection and AR12, an inhibitor of chaperones including GRP78 suppressed SARS-CoV-2 infection (15). Collectively, these results suggest that through targeting host auxiliary chaperones such as GRP78 required for viral entry and production could offer a new strategy toward the development of broad spectrum anti-viral therapy.…”
Section: Resultsmentioning
confidence: 99%
“…2G ). Interestingly, a recent study showed GRP78 co-localizing with SARS-2-S following live virus infection and AR12, an inhibitor of chaperones including GRP78 suppressed SARS-CoV-2 infection (15). Collectively, these results suggest that through targeting host auxiliary chaperones such as GRP78 required for viral entry and production could offer a new strategy toward the development of broad spectrum anti-viral therapy.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the exact mechanisms underlying the role of autophagy in the emerging hCoV life cycle need further investigation. Some autophagy-based inhibitors demonstrate encouraging therapeutic potential against SARS-CoV-2 infections [ 50 , 53 ]. Therefore, repurposing of approved and well-tolerated drugs targeting autophagy would offer a welcome shortcut to rapidly develop treatments against COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Bouhaddou et al recently reported that the pharmacological inhibitors of p38/MAPK signalling and PIKFYVE downstream of PIK3CA/AKT were found to possess strong antiviral efficacy in Vero E6 and A549-ACE2 cells infected with SARS-CoV-2 [ 48 ]. Rayner et al also demonstrated that AR12 (OSU-03012), a derivative of celecoxib, suppressed the production of infectious virions by enhancing autophagic flux in SARS-CoV-2 infected Vero cells [ 53 ]. Additionally, a recent preprint article from Gassen et al presented that autophagy activation can suppress viral propagation in SARS-CoV-2 infected NCI-H1299 and Vero FM cells by using the pro-autophagic compound spermidine and the AKT inhibitor MK-2206 [ 50 ].…”
Section: Coronavirus Infections and Autophagymentioning
confidence: 99%
See 1 more Smart Citation
“…Compound 26 decreases ACE2 and GRP78 expression in the cell surface and total GRP78 levels. Compound 26 not only catalytically inhibits the GRP78 ATPase activity but also reduces the chaperone proteins, which are linked with low S protein and the production of infectious virions ( Rayner et al, 2020 ).…”
Section: Targeting the S Proteinmentioning
confidence: 99%